A STUDY ON THE PATTERN OF SPINE TRAUMA IN PATIENTS PRESENTED TO KHYBER TEACHING HOSPITAL - KHAN , SU; ALI , H; SAEED , F; ULLAH , I; ALI , M (Biological and Clinical Sciences Research Journal, 2023)
This study was conducted to assess the pattern of spine trauma in patients presenting to Khyber Teaching Hospital in terms of etiology, level of injury, type of fracture, and neurologic deficit. This cross-sectional study was conducted at the Department of Orthopedic Surgery at Khyber Teaching Hospital, Peshawar. Patients presenting with spinal cord injuries were included. Etiology, level of injury, types of fracture, and the neurologic deficit were recorded and assessed. The Chi-square test was used to assess the association. The mean age of the patients was 33.28±9.63 years. There were 88 (69.3%) males and 39 (30.7%) females. Fall from height (50.4%) was the most prevalent etiology, followed by RTA (30.7%). Thoracolumbar spine injury (49.6%) was the most prevalent level of spinal injury, followed by cervical spine injury (29.9%). Most patients had type A fractures 43.3%), and type B (37%) was the second leading fracture. The neurologic deficit was seen in 54.3% of patients. Fall from height is the most common cause of spinal traumas in our country, and road traffic accidents are the second leading cause. Thoracolumbar spine injury was the primary presentation of the spinal injury location, and type A was the most common type of fracture. The majority of the patients had a neurologic deficit.